Josephus and the politics of historiography : apologetic and impression management in the Bellum Judaicum - Mader, Gottfried. (Mnemosyne, Supplements, 2000)
Although Josephus' debt to the traditions of Greco-Roman historiography is widely recognized, the classical elements in his Bellum Judaicum are still often dismissed as just formal ornatus . This study reconsiders Josephus' intellectual affiliation to his predecessors in the genre and argues that the work's classical complexion, and in particular its distinctive color Thucydideus , are integral to the intellectual and ideological design of BJ . Deployed typically at crucial points where Josephus deals with the motives of the Jewish insurgents, the classical elements directly subserve the work's apologetic and polemical tendencies, subtly predisposing the reader to a particular interpretation by applying the rationalist and psychological categories of 'scientific' Greek historiography. In this sense the classical form of BJ is interpreted in light of the historian's partisan political agenda.